Impact of green brand authenticity on warm glow, green satisfaction, and willingness to pay more - Hyoungeun, Moon; Jongsik, Yu; Chua, Bee-Lia; Han, Heesup (Taylor & Francis, 2023)
This study explored the concept of green brand authenticity in tourism and its relationships with relevant variables by using a mixed method. Firstly, the content analysis of interview revealed four dimensions of green brand authenticity: green practice, green servicescape, green support for locals, and green customer engagement. Then, the analysis of a total of 352 survey responses collected through an online research panel uncovered brand-self congruence as the most significant antecedent of green brand authenticity and green customer engagement as the most impactful dimension on the outcome variables. Brand commercialization significantly moderated the relationships among the study variables.